Insect herbivory, plant defense, and early Cenozoic climate change - Wilf, Peter (The National Academy of Sciences, 2001)
Insect damage on fossil leaves from the Central Rocky Mountains, United States, documents the response of herbivores to changing regional climates and vegetation during the late Paleocene (humid, warm temperate to subtropical, predominantly deciduous), early Eocene (humid subtropical, mixed deciduous and evergreen), and middle Eocene (seasonally dry, subtropical, mixed deciduous and thick-leaved evergreen). During all three time periods, greater herbivory occurred on taxa considered to have short rather than long leaf life spans, consistent with studies in living forests that demonstrate the insect resistance of long-lived, thick leaves. Variance in herbivory frequency and diversity was highest during the middle Eocene, indicating the increased representation of two distinct herbivory syndromes: one for taxa with deciduous, palatable foliage, and the other for hosts with evergreen, thick-textured, small leaves characterized by elevated insect resistance. Leaf galling, which is negatively correlated with moisture today, apparently increased during the middle Eocene, whereas leaf mining decreased.